QT dispersion in renal transplant recipients - FAK, ALİ SERDAR; KOÇ, MEHMET (KARGER, 2002)
An increased QT dispersion (QTd) is associated with a variety of cardiac diseases and predicts sudden death. Although chronic renal failure patients and patients on hemodialysis are shown to have an increased QTd, evidence of increased QTcl in renal transplant patients is scarce. In this study, renal transplant patients were evaluated to find out if they had an increased QTd. Thirty-four renal transplant recipients aged 35 8 years and 34 healthy control subjects aged 34 8 years were included in the study. The mean time after transplantation was 51.8 +/- 40.4 (range 5-154) months. The QT interval was measured by 12-lead electrocardiogram, and the QTd was defined as the difference between the maximum and minimum QT interval. Bazett's formula was used to correct for the heart rate (QTc). Both QTcl and QTc dispersion (QTcd) in renal transplant patients were compared with those of control subjects. All patients underwent transthoracic echocardiographic assessment and 24-hour ambulatory blood pressure monitoring. Renal transplant recipients had similar QTd (37 +/- 15 vs. 39 +/- 17 ms) and QTcd (50 +/- 18 vs. 55 +/- 20 ms) compared to control subjects. QTd and QTcd were similar in patients with and without left ventricular hypertrophy (QTd 37 +/- 14 vs. 36 +/- 17 ms and QTcd 50 +/- 14 vs. 49 +/- 21 ms, respectively). No association was found between QTcl and left ventricular mass index or blood pressure measurements. The QTd was not found to be increased in renal transplant recipients as compared with that of healthy controls in this study. Normalization of the QTcl after renal transplantation may be through the correction of several factors responsible for increased QTd in uremic patients. Copyright (C) 2002 S. KargerAG, Basel.
Keywords: QT dispersion; renal transplantation; arrhythmia; hypertension; left ventricular hypertrophy; LEFT-VENTRICULAR HYPERTROPHY; HEART-RATE-VARIABILITY; CARDIAC-ARRHYTHMIAS; INTERVAL DISPERSION; HEMODIALYSIS; FAILURE; DEATH; REPOLARIZATION; PRESSURE; RISK